If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -2 = 6 + -1n Reorder the terms: -2 + 3n = 6 + -1n Solving -2 + 3n = 6 + -1n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add 'n' to each side of the equation. -2 + 3n + n = 6 + -1n + n Combine like terms: 3n + n = 4n -2 + 4n = 6 + -1n + n Combine like terms: -1n + n = 0 -2 + 4n = 6 + 0 -2 + 4n = 6 Add '2' to each side of the equation. -2 + 2 + 4n = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 4n = 6 + 2 4n = 6 + 2 Combine like terms: 6 + 2 = 8 4n = 8 Divide each side by '4'. n = 2 Simplifying n = 2
| 5x^2=3+2x | | x+3=10x | | 0.8x-2.6=1.7x+1.5 | | x+11x+8= | | 5m+1=13-m | | 1/2x+1/4=12 | | 0.12(y-7)+0.06y=0.02y-1.8 | | 4t-3=t+9 | | x+13x+30= | | -(x-1)=-2(-x-1)-4 | | X/6x-1=5 | | 3x^2=3+8x | | X/6x-1=5/1 | | x+11x+28= | | 02.0x+0.35(50)=22.5 | | -172+-8w+4y^2=0 | | 2k-1=k+7 | | x+4/7=x-2/5 | | 17x-13y=7 | | 6+3(x-7)=82 | | 3y+5=13-y | | 7y+3=3y+5 | | 17x+13y=7 | | 5/6x+6/5=-6/5 | | O(10)=2*10-1 | | 495/x=55 | | 2x*3-3-3-3=10 | | (x-2)=4(-4x-5) | | 4(3-x)-3(2-x)=9 | | 4/5x+6/5=-6/5 | | 3x+2/5 | | (3+v)(2v-7)=0 |